Resistance to Anti-Cancer Therapeutics Targeting Receptor Tyrosine Kinases and Downstream Pathways (Resistance to Targeted Anti-Cancer Therapeutics,, 2018)
This volume comprehensively covers the multiplicity and diversity of mechanisms underlying patient resistance to currently approved anti-cancer drugs, including tyrosine kinase inhibitors and monoclonal antibodies, blockers of growth factor receptors and their downstream pathways, which play essential functions in cancer progression. Each chapter will cover a specific group of targets and the cognate drugs, along with molecular modes of innate and evolving resistance.